a EFFECT OF DIFFERENT ADDITIVES ON METALLIC LEAD RECOVERY FROM CRT FUNNEL GLASS USING THERMAL METHOD : abstract, introduction, mathematical and experimental models, results and discussion, conclusions (THE IRAQI JOURNAL FOR MECHANICAL AND MATERIALS ENGINEERING, 2020)
Cathode ray tube like as electronic waste is a green crisis due to its toxicity. Remove of the lead from CRT funnel glass can prevent it from release into the environmental and allow it reuse. There are several ways to separation lead from its CRT funnel glass and then recovered from it. In this research, CRT funnel glass was treated by high thermal reduction method with using different additives. These additives that used in this method are sodium carbonate (Na2CO3 ) with (20, 25&30) wt% used as a melting agent, sodium sulfide ( Na2S) with (6, 8&10)wt% used as a catalytic agent and carbon powder (C) with (2.4, 3.6 &4.8) wt% used as a reducing agent, at fixed temperature (1100°C) and holding time (120 min). Taguchi technique for design of experiment (DOE) was applied to find the optimum process conditions of different additives for metallic lead recovery by high thermal reduction method. Experimental results presented that the maximum lead recovery was 97.36% when the optimum conditions were sodium carbonate (30%), sodium sulfide (10%), and carbon powder (3.6%) at 1100°C and 120 min.